Utilization of Tamarind Seed Testa - Ramachandra Rao, P. (Indian Forester, 1957)
An alkaline cutch has been prepared from the tamarind seed testa. A pilot-scale trial of the cutch in the oil drilling operations in the Assam Oil Co., Digboi has shown that the amount required to get comparable effects on mud is more than three times that of Acacia cutch. The ultimate use of the tamarind seed testa in the oil-drilling operations is indicated.